IMPROVING TOURISM BUSINESS PERFORMANCE THROUGH GREEN MARKET ORIENTATION, IT ADOPTION CAPABILITY, AND GREEN INNOVATION - Nugroho, Arif; Mulyani, Sri; Usman, Miftahudin (Universitas Nusa Cendana, 2025)
This research aims to investigate the impact of green market orientation on the development of IT adoption capability and subsequently green innovation. This research identifies important factors that influence higher business performance in response to environmental pressures. The research examines 216 tourism firms operating in the Greater Jakarta area to provide confirmation on the constructs’ relationships under observation. It is done using structural equation modelling (SEM) to confirm the validity and reliability of the measurement and structural model. The study suggests that green market orientation positively affects the building of IT adoption capability and encourages green innovation. Firms‘ decisions to develop both capabilities are not affected by stakeholders’ environmental pressure. This research also found that IT adoption capability alone could not improve business performance. Green innovation is critical to mediate the two constructs. Suggestions are listed for future research. Keywords: Green Market Orientation; IT Adoption Capability; Green Innovation; Stakeholders’ Environmental Pressure; Business Performance.